The Morbidity Costs of Air Pollution through the Lens of Health Spending in China - Xin Zhang; Xun Zhang; Yuehua Liu; Xintong Zhao; Xi Chen (Institute of Labor Economics (IZA), 2022)
This study is one of the first investigating the causal evidence of the morbidity costs of fine particulates (PM2.5) for all age cohorts in a developing country, using individual-level health spending data from a basic medical insurance program in Wuhan, China. Our instrumental variable (IV) approach uses thermal inversion to address potential endogeneity in PM2.5 concentrations and shows that PM2.5 imposes a significant impact on healthcare expenditures. The 2SLS estimates suggest that a 10 μg/m3 reduction in monthly average PM2.5 leads to a 2.36% decrease in the value of health spending and a 0.79% decline in the number of transactions in pharmacies and healthcare facilities. Also, this effect, largely driven by the increased spending in pharmacies, is more salient for males and children, as well as middle-aged and older adults. Moreover, our estimates may provide a lower bound to individuals' willingness to pay, amounting to CNY 43.87 (or USD 7.09) per capita per year for a 10 μg/m3 reduction in PM2.5.
Keywords: Q51; Q53; I11; I31; 330; air quality; health spending; willingness to pay; China